2015
DOI: 10.1016/j.cjtee.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

The management of naso-orbital-ethmoid (NOE) fractures

Abstract: The bony naso-orbital-ethmoid (NOE) complex is a 3-dimensional delicate anatomic structure. Damages to this region may result in severe facial dysfunction and malformation. The management and optimal surgical treatment strategies of NOE fractures remain controversial. For a patient with NOE trauma, doctors should perform comprehensive clinical examination and radiographic analysis to assess the type and extent of fracture. The results of assessment will assist doctors to make a patient-specific program for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 56 publications
1
7
0
5
Order By: Relevance
“…The extensive dissection and elevation of important midfacial structures and the skin-soft tissue envelope should not be performed if it can be avoided. 56,[59][60][61] Fracture patterns can be described using the Markowitz classification (►Table 1). This classification scheme defines NOE fractures on the basis of the MCT attachment to the central fragment.…”
Section: Naso-orbito-ethmoid Fracturesmentioning
confidence: 99%
“…The extensive dissection and elevation of important midfacial structures and the skin-soft tissue envelope should not be performed if it can be avoided. 56,[59][60][61] Fracture patterns can be described using the Markowitz classification (►Table 1). This classification scheme defines NOE fractures on the basis of the MCT attachment to the central fragment.…”
Section: Naso-orbito-ethmoid Fracturesmentioning
confidence: 99%
“…Late treatment of this type of fracture may result in secondary deformities, including a shortened and retruded nose, enophthalmia, telecanthus and ocular dystopia. Diagnosis is based on clinical and imaging exmonitoring by means of computed tomography (Wei, et al, 2015). Some studies have reported that both the mandible (Glapa, et al, 2007;Cohen, Shakenovsky & Smith, 1986) and the zygoma (Hollier, Grantcharova & Kattash, 2001) are the most commonly injured facial bones in high-intensity trauma.…”
mentioning
confidence: 99%
“…θαζζαε δεΪ,ΝβΝπαλαπΪθωΝαπσ α βΝπλΫπ δΝθαΝδ οτ αδΝη Ν οΝηδ σΝ βμΝ δαεολλδεάμΝ απσ α βμΝ Νφυ δοζοΰδεΪΝΪ οηαέ ΗΝπαλαπΪθωΝεα Ϊ α βΝηπολ έΝθαΝχαλαε βλδ έΝ εαδΝ ωμΝ ηφΪθδ βΝ ηοΰΰοζο δ οτμΝ φολΪμΝ βμΝ η οίζ φΪλδαμΝ χδ ηάμέ Ν π λέπ ω βΝ σπουΝ υθυπΪλχ δΝ εΪ αΰηαΝ ουΝ πλσ γδουΝ ελαθδαεοτΝ ίσγλουΝ ΧπχΝ λδηΫθοΝ πΫ αζοΝ βγηο δ οτμΝ ο οτ,Ν Ϋ αφομΝ η ωπδαέουΝ εσζπουΨΝ ηπολ έΝ θαΝ υθυπΪλχουθΝ αΝ ιάμ: δα αλαχάΝ πδπΫ ουΝ υθ έ β βμ,Ν πθ υηο ΰεΫφαζομ,Ν λδθσλλοδαΝ ΰε φαζοθω δαέουΝ υΰλοτ,ΝπαγοζοΰδεάΝθ υλοζοΰδεάΝ βη δοζοΰέα,Ν θ οελΪθδαΝαδηολλαΰέαΝάΝαδηΪ ωηαέΝΗΝ απ δεσθδ βΝ ωθΝ λδθοεοΰχοβγηο δ δευθΝ εα αΰηΪ ωθΝ ΰέθ αδΝ ωμΝ πέΝ οΝ πζ έ οθΝ η Ν αιοθδεάΝ οηοΰλαφέαΝ πζαχθδεοτΝελαθέου,Ν θυΝη ΰαζτ λβΝαελέί δαΝ πδ υΰχΪθ αδΝη Ν βθΝ λδ δΪ α βΝ αθα τθγ βΝ ωθΝ παλαπΪθωΝ οηυθέΝ ΗΝ ηαΰθβ δεάΝ οηοΰλαφέαΝ ηπολ έΝ θαΝ έθαδΝ υθ πδεουλδεάΝ σ οθΝ αφολΪΝ βθΝ θ σπδ βΝ εαευ ωθΝ ωθΝ ηαζαευθΝ ηολέωθΝ ουΝ οφγαζηδεοτΝ εσΰχουΝ άΝ υθο υθΝ εαευ ωθΝ ουΝ ΰε φαζδεοτΝ παλ ΰχτηα ομέΝ ΟΝ εζα δεσμΝ αε δθοζοΰδεσμΝ Ϋζ ΰχομΝ η Ν απζΫμΝ αε δθοΰλαφέ μΝ δαφσλωθΝπλοίοζυθΝ ουΝελαθέουΝαπο ζ έΝευλέωμΝ βθΝαλχδεάΝπλο Ϋΰΰδ β (Heine RD et al, 1990, Markowitz BL et al, 1991, Watkinson JC et al, 2018, Wei JJ et al, 2015, Κωθ αθ δθέ βμΝΙΝεαδΝ υθ, 2013. παλ ε σπδ αΝλδθοεοΰχοβγηο δ δεΪΝεα Ϊΰηα αΝάΝεα Ϊΰηα αΝηδελάμΝ παλ ε σπδ βμΝ εα ΪΝMarkowitz I ηπολοτθΝθαΝαθ δη ωπδ οτθΝησθοΝ υθ βλβ δεΪΝη Ναποδ βηα δεΪ,Ν αθ δίδο δεΪΝεαδΝαποφυΰάΝ ηφτ β βμΝλδθσμΝΰδαΝ1ί-1ηΝηΫλ μέΝΩ σ ο,Ν οΝη ΰαζτ λοΝ πο ο σΝαπαδ έΝχ δλουλΰδεάΝαθ δη υπδ β η Ναθοδε άΝαθΪ αιβΝ εαδΝ αγ λοποέβ βΝ η Ν χλά βΝ ω λδεάμΝ ο ο τθγ βμΝ Χεα ΪΝ πλο έηβ βΝ η Ν mini plate άΝ τληα αΨέΝ Μπολ έΝ πέ βμΝθαΝαπαδ βγ έΝβΝχλά βΝο δεοτΝηο χ τηα ομΝάΝ θγΫηα ομέΝΟδΝ υθάγ δμΝ πλο π ζΪ δμΝ πουΝ χλβ δηοποδοτθ αδΝ έθαδΝ οδΝ ιάμ: εα ΪΝ Lynch,Ν Ν δ πδπ φυεο δεά,Ν υποίζ φαλδ δεάΝ άΝ ηΫ βΝ υποίζ φαλδ δεά,Ν υποεσΰχδα, αηφδελο αφδεάΝ άΝ φαθδαέα.…”
Section: κασαγμασανπλαχνικοτνκρανιοτunclassified
“…παλ ε σπδ αΝλδθοεοΰχοβγηο δ δεΪΝεα Ϊΰηα αΝάΝεα Ϊΰηα αΝηδελάμΝ παλ ε σπδ βμΝ εα ΪΝMarkowitz I ηπολοτθΝθαΝαθ δη ωπδ οτθΝησθοΝ υθ βλβ δεΪΝη Ναποδ βηα δεΪ,Ν αθ δίδο δεΪΝεαδΝαποφυΰάΝ ηφτ β βμΝλδθσμΝΰδαΝ1ί-1ηΝηΫλ μέΝΩ σ ο,Ν οΝη ΰαζτ λοΝ πο ο σΝαπαδ έΝχ δλουλΰδεάΝαθ δη υπδ β η Ναθοδε άΝαθΪ αιβΝ εαδΝ αγ λοποέβ βΝ η Ν χλά βΝ ω λδεάμΝ ο ο τθγ βμΝ Χεα ΪΝ πλο έηβ βΝ η Ν mini plate άΝ τληα αΨέΝ Μπολ έΝ πέ βμΝθαΝαπαδ βγ έΝβΝχλά βΝο δεοτΝηο χ τηα ομΝάΝ θγΫηα ομέΝΟδΝ υθάγ δμΝ πλο π ζΪ δμΝ πουΝ χλβ δηοποδοτθ αδΝ έθαδΝ οδΝ ιάμ: εα ΪΝ Lynch,Ν Ν δ πδπ φυεο δεά,Ν υποίζ φαλδ δεάΝ άΝ ηΫ βΝ υποίζ φαλδ δεά,Ν υποεσΰχδα, αηφδελο αφδεάΝ άΝ φαθδαέα. ΓδαΝ βθΝαποεα Ϊ α βΝ ουΝΫ ωΝεαθγοτΝηπολ έΝθαΝπλαΰηα οποδβγ έΝεαθγοπβιέαέΝ Ν υθτπαλιβΝεΪεω βμΝ ουΝοφγαζηδεοτΝίοζίοτΝαπαδ έ αδΝοφγαζηδα λδεάΝγ λαπ υ δεάΝ πλο Ϋΰΰδ βέΝ Ν υθτπαλιβΝ εΪεω βμΝ ουΝ λδθο αελυρεοτΝ υ άηα ομΝ απαδ έ αδΝ υθ υα ησμΝ οφγαζηδα λδεάμΝ εαδΝ θ ο εοπδεάμΝ ω ολδθοζαλυΰΰοζοΰδεάμ γ λαπ υ δεάμΝπλο Ϋΰΰδ βμέΝ Ν υθτπαλιβΝεΪεω βμΝ ουΝη ωπολλδθδεοτΝπσλουΝάΝ ουΝ η ωπδαέουΝ εσζπουΝ ηπολ έΝ θαΝ απαδ βγ έΝ θ ο εοπδεάΝ άΝ αθοδε άΝ ω ολδθοζαλυΰΰοζοΰδεά γ λαπ υ δεάΝ πλο Ϋΰΰδ βΝ ουΝ αθ έ οδχουΝ παλαλλέθδουΝ εσζπουΝ Ναπυ λοΝχλσθο (Lu GN et al, 2017, Markowitz BL et al, 1991, Smith B, 1976, Watkinson JC et al, 2018, Wei JJ et al, 2015, Κωθ αθ δθέ βμΝΙΝεαδΝ υθ, 2013.…”
Section: κασαγμασανπλαχνικοτνκρανιοτunclassified
See 1 more Smart Citation